Laporan pendekatan kajian Carrying capacity pulau-pulau peranginan Semenanjung Malaysia - Husin, Ahmad Tarmizi; Talib, Rosmin; Raja Othman, Raja Norashekin; Asmawi, M. Zainora; Yahya, Zaki; Asmawi, M. Zainora; Idrus, Rosli; Saad, Zulkifli; Husain, Nooreha; Hamid, Naidatul Azima; Ibrahim, Mahiran; Md Said, Hairi; et al. (PLANMalaysia, Jabatan Perancangan Bandar dan Desa, 2019)
This report addresses the fundamental framework of the study covering the relevance policies, methods and detailed study plan for respective sectors involved in the study. The report also discusses about some case studies and techniques for data analysis.